Analisis Strategi Promosi Melalui Pemanfaatan Media Sosial dalam Upaya Peningkatan Omzet Penjualan: Studi pada Coffee Shop Kateko Surabaya - Erika Anjani Widianti; Lia Nirawati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research was conducted with the aim of knowing and analyzin g the promotional strategy at Kateko Surabaya coffee shop, which is one of the business sectors in the field of food and beverages (FnB). The research method used is descriptive qualitative method using SWOT analysis techniques and data collection techniques through in-depth interviews, observation and documentation related to promotional strategies that are useful for identifying strengths, weaknesses, opportunities, and threats at Kateko coffee shop. The informants in this research include of owners, employees, and consumers. The results of the research analysis using IFAS show that Kateko's coffee shop has strength factors receiving a total score of 2.87 and weakness factors receiving a total score of 0.42. While the EFAS results show that threats get a total score of 0.80, while opportunities get a total score of 2.10. Based on the SWOT analysis diagram, kateko coffee shop is in quadrant I with a value of X; Y) (2.45; 1.30), which indicates that the company uses a SO strategy, namely the company has opportunities and strengths so that it can take advantage of existing opportunities. The strategy that can be applied is to support an aggressive growth policy (growth oriented strategy) in increasing sales.